The influence Sejahtera socio-economic factors on purchasing of Kuala Lumpur affordable houses among middle income earners - Ahmad, Anisah; Mhd. Sarif, Suhaimi (SEJAHTERA CONSUMERISM, KENMS, IIUM, 2023)
Housing is an essential and basic need of people. There have to be efforts and schemes to enable people to own a house for shelter. This issue has been discussed as affordable housing in academia and practice. Notably, there are sejahtera socio-economic factors influencing affordable housing for a certain group of people, particularly the middle income earners. The study explores on the sejahtera social economic factors that influenced the price of affordable housing in Kuala Lumpur. The key social factors can be discussed into the dilemma of the middle income earners who are eligible for home loans but unable to meet the financial commitment on a long term basis, the role of the housing authority, and the preference of house developers and financial institutions for home loan. These factors led to high prices for the affordable house category in the absence of strict regulations and policies for affordable houses in the Kuala Lumpur area. This study employed personal interviews with selected respondents who are middle-income earners from Kuala Lumpur. Prior to the interview, the study conducted research instrument validation with experts and a pilot test to ensure reliability, validity, trustworthiness, and reliability. The study finds that major socio-economic factors that influenced high prices for affordable houses in Kuala Lumpur are the commercial preference of house developers, architectural design choices, friendly foreign buyers’ incentives, and lack of regulatory support from relevant authorities. This study recommends a revision in the existing policies for affordable housing schemes with more incentives to the housing developers and flexible financial schemes for house buyers among middle income earners. For future studies, the study could include more respondents from other big cities.